2015
DOI: 10.1080/17439884.2015.1064954
|View full text |Cite
|
Sign up to set email alerts
|

Social media and education: reconceptualizing the boundaries of formal and informal learning

Abstract: It is argued that social media has the potential to bridge formal and informal learning through participatory digital cultures. Exemplars of sophisticated use by young people support this claim, although the majority of young people adopt the role of consumers rather than full participants. Scholars have suggested the potential of social media for integrating formal and informal learning, yet this work is commonly under-theorized. We propose a model theorizing social media as a space for learning with varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
272
0
20

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 506 publications
(297 citation statements)
references
References 58 publications
5
272
0
20
Order By: Relevance
“…However, as Gibson (2008) argued, TPACK can also be characterised as a learning environment or educative experience, and it is thus legitimate to conceive learning in this characterisation as having varying attributes of formality and informality (Greenhow & Lewin, 2016). This notion of TPACK beyond the knowledge perspective is especially germane to pre-service teachers because pedagogical practices requiring formal and informal learning are common and necessary.…”
Section: / 12mentioning
confidence: 99%
See 1 more Smart Citation
“…However, as Gibson (2008) argued, TPACK can also be characterised as a learning environment or educative experience, and it is thus legitimate to conceive learning in this characterisation as having varying attributes of formality and informality (Greenhow & Lewin, 2016). This notion of TPACK beyond the knowledge perspective is especially germane to pre-service teachers because pedagogical practices requiring formal and informal learning are common and necessary.…”
Section: / 12mentioning
confidence: 99%
“…As informal learning is facilitated by the environment and its supporting structures, social media tools are ideal platforms. In particular, Greenhow and Lewin (2016) argued that although the boundary between formal and informal learning is becoming increasingly blurred, social media provide a possible approach to bridge the two learning opportunities through participatory digital cultures (Jenkins, Purushotma, Weigel, Clinton, & Robinson, 2009) where the distinction between "selfdirected, intentional learning and spontaneous, incidental and experiential learning" (p. 8) becomes less clear. Dabbagh and Kitsantas (2012) developed a three-level pedagogical framework to integrate formal and informal learning through social media and support students' self-regulated learning in higher education.…”
Section: Social Media and Informal Learningmentioning
confidence: 99%
“…Social media has the potential to bridge formal and informal learning through participatory digital cultures (Greenhow & Lewin, 2016). Our research showed that only students exploit virtual social spaces for ubiquitous learning.…”
Section: Discussionmentioning
confidence: 98%
“…Our research showed that only students exploit virtual social spaces for ubiquitous learning. Greenhow and Lewin (2016) described two different perspectives on young people's social media use, and in both cases elements of self-determination in learning purpose and self-direction of learning process was established. For our research participants, selfdirection of learning was also expressed, but some learners (both teachers and students) lacked motivation and final learning targets.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of blurring boundaries in formal and informal pedagogical practices increases, and formal and informal learning converge within the social media (Greenhow & Lewin, 2016). Complex student-teacher relationships and interactions predict academic achievements (Crosnoe, Johnson, & Elder, 2004).…”
Section: Introductionmentioning
confidence: 99%